COST ANALYSIS OF TUBERCULOSIS CONTROL ACTIVITIES CENTERED AT THE PATIENT AND PERFORMED ON THE OUT-PATIENT BASIS IN THE URBAN SETTINGS - I. E. Gelmanova; N. A. Zemlyanaya; A. B. Yedilbaev; E. A. Kruk (Туберкулез и болезни лёгких)
Costs of out-patient patient-centered activities introduced into the existing standard model of the tuberculosis treatment have been evaluated in Tomsk TB Service. Additional measures enhancing compliance in the patients included the following: timely detection and management of side effects of chemotherapy, social support to the patients, treatment at home, psychological support and treatment by the Sputnik team of most socially vulnerable patients.The average additional costs for the patient-centered activities per 1 patient treated as per regimens I, II, III made 1367 RUR a month; per 1 PR TB patient – 2978 RUR; and per regimen IV – 4865 RUR. Patient-centered activities performed during the out-patient stage of treatment made 7% out of the total treatment costs for regimens I, II, III; 14% when treating polyresistant TB; and 16% for regimen IV.